Tripodal molecular propellers perturb microtubule dynamics: indole acts as a blade and plays a crucial role in anticancer activity. Issue 16 (6th February 2019) - Barman, Surajit; Das, Gaurav; Mondal, Prasenjit; Pradhan, Krishnangsu; Jana, Batakrishna; Bhunia, Debmalya; Saha, Abhijit; Kar, Chirantan; Ghosh, Surajit
Abstract : A microtubule targeted tripodal molecular propeller has been constructed having indoles as appendages. It strongly interacts at the DCVJ site of tubulin and controls the dynamicity of microtubule. Abstract : An indole-rich tripodal microtubule inhibitor is designed, which binds at the DCVJ site of tubulin and inhibits its polymerization. It causes apoptotic death of cancer cells without affecting normal cells and inhibits the growth of tumors. Finally, STD-NMR and TR-NOESY experiments reveal that the indole appendages play a crucial role in interacting with tubulin.